Oro temperatūros išvestinės priemonės: naudojimo galimybės Lietuvos ūkyje - Kropienė, Rūta; Jurgo, Gžegož (Lietuvos statistikos darbai, 2010)
The impact of weather on many commercial and recreational activities is significant and varies both geographically and seasonally. Many industries, including agriculture, energy, utility, construction, tourism and other businesses, are either favourably or adversely affected by “bad” weather. For this reason, financial markets have devised a relatively new class of instruments, the so-called “weather derivatives”, the first of which were launched in 1996 in the United States. There is a number of factors behind the growth in the weather derivatives market. One of these is the deregulation of energy markets. Another one is that capital and insurance markets have come closer to each other. A weather derivative is the newest product of the financial derivatives market. It allows a market participant to minimise a risk from daily weather fluctuations, while insurance companies sell insurance against catastrophic events. The main aim of this article is to explore possibilities to use weather derivatives for the Lithuanian economy. To reach the aim, the following goals were set: to describe products of weather derivatives and their features and to present the possibilities to use these derivatives in the Lithuanian economy on the basis of an example of temperature derivatives. A hypothesis is made that Lithuanian companies could discover new possibilities for business management through the use of weather derivatives. The methods used in the paper are as follows: comparative analysis, indexes, regression and correlation analysis.